Cyclin-dependent Kinase-mediated Sox2 Phosphorylation Enhances the Ability of Sox2 to Establish the Pluripotent State - Ouyang, Juan (J Biol Chem, 2015)
Sox2 is a key factor in maintaining self-renewal of embryonic stem cells (ESCs) and adult stem cells as well as in reprogramming differentiated cells back into pluripotent or multipotent stem cells. Although previous studies have shown that Sox2 is phosphorylated in human ESCs, the biological significance of Sox2 phosphorylation in ESC maintenance and reprogramming has not been well understood. In this study we have identified new phosphorylation sites on Sox2 and have further demonstrated that Cdk2-mediated Sox2 phosphorylation at Ser-39 and Ser-253 is required for establishing the pluripotent state during reprogramming but is dispensable for ESC maintenance. Mass spectrometry analysis of purified Sox2 protein has identified new phosphorylation sites on two tyrosine and six serine/Threonine residues. Cdk2 physically interacts with Sox2 and phosphorylates Sox2 at Ser-39 and Ser-253 in vitro. Surprisingly, Sox2 phosphorylation at Ser-39 and Ser-253 is dispensable for ESC self-renewal and cell cycle progression. In addition, Sox2 phosphorylation enhances its ability to establish the pluripotent state during reprogramming by working with Oct4 and Klf4. Finally, Cdk2 can also modulate the ability of Oct4, Sox2, and Klf4 in reprogramming fibroblasts back into pluripotent stem cells. Therefore, this study has for the first time demonstrated that Sox2 phosphorylation by Cdk2 promotes the establishment but not the maintenance of the pluripotent state. It might also help explain why the inactivation of CDK inhibitors such as p53, p21, and Arf/Ink4 promotes the induction of pluripotent stem cells.